(3OjhGf EHQGgje GdYWGQs - (3EHQGgje Hf eMeO GdYWGQ Hf Ydj GdMSjfj GdcGXej,J (B1230 (3g` s
(3ChdgG (B:s
((3bGd LGeYg(B) (3LeYJ eG JecfJ efg hQJHJg Ydi aUdjf(B: (3GdaUd GdChd aj Phj GdYUeI Ydjge GdSdGe, hGdKGfj aj ZjQge s
(3BNQgG (B:s
(3ef JTWjQI bUjOI GdTjN EHQGgje jMji aj CMeO CZG MGce HZOGO aeG CfTOJ EdG hCgOJ fhGaNG Edi GdCfa dcf aGQI GdeSc CVhY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B13 s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(293) s
Keywords: (3GdCOHs